Batteries: An Advanced Na–FeCl2 ZEBRA Battery for Stationary Energy Storage Application (Adv. Energy Mater. 12/2015). Issue 12 (June 2015) - Li, Guosheng; Lu, Xiaochuan; Kim, Jin Y.; Viswanathan, Vilayanur V.; Meinhardt, Kerry D.; Engelhard, Mark H.; Sprenkle, Vincent L.
<x xml:space="preserve">Abstract</x> In article number 1500357, Guosheng Li, Jin Y. Kim, and co‐workers report a remarkably reliable Na‐FeCl2 ZEBRA battery for stationary energy storage applications. The removal of surface oxide passivation layers on iron particles is critical and it is attributed to polysulfide species generated from sulfur‐based additives through polysulfide reactions. The Na‐FeCl2 cells presented can be assembled at the discharge state (NaCl + Fe powder) without handling highly hazardous materials such as anhydrous FeCl2 and metallic sodium.